The composition and properties of jenny milk - Željka Cvrtila Fleck; Jelena Sigurnjak; Vanda Siročić; Bela Njari; Miroslav Benić; Jelka Pleadin; Maja Popović; Lidija Kozačinski (Mljekarstvo)
Jenny breeding and the production of jenny milk are becoming more common, especially on family farms in the area of Istria and Dalmatia, but in continental Croatia as well. The aim of this study was to explore basic chemical and fatty acid composition, somatic cell count and sensory traits of jenny milk. In total eleven milk samples were analized from two breeds: Littoral-Dinaric (Dalmatian) jennies (N=6) and Istrian jennies (N=5) originating from farms in the area of Zagreb and Istrian County. Fat content was markedly low and was 1.16 % at the most, whereas the average fat content in the milk of Istrian jennies was 0.14 %, i.e. 0.69 % in Dalmatian jennies. The average protein content was 1.29 % and average lactose content 6.5 %. The milk of Dalmatian jennies contained 3.8 log10 mL-1 of somatic cells whose values were lower in the milk of Istrian jennies (3.2 log10 mL-1). At the same time a higher total count of white blood cells (4.9-5.3 x 109/L) was determined in milk samples of Istrian jennies, in comparison to the milk of Dalmatian jennies (5.1 x 109/ L at the most). The fatty acid composition showed that the content of saturated fatty acids (SFA) in the milk of Istrian jennies was 70.45 %, while in the milk of Dalmatian jennies it was 59.92 %. The monounsaturated fatty acids (MUFA) were represented on average with 21.23 % and 24.61 %, while polyunsaturated fatty acids (PUFA) with 8.31 % and 15.46 % in Istrian and Dalmatian jennies. The total ratio saturated/unsaturated fatty acids ranged from 0.37 to 0.72 at the most and it was lower in milk samples of Istrian jennies. Jenny milk is characterized by a low fat content and high lactose content, and fatty acid composition with a favourable ratio of saturated and unsaturated fatty acids. The somatic cell count in the milk is lower in comparison to the milk of other domestic animals.